Surface modified rare earth doped cesium tungsten bronze and application thereof in preparation of multicolor light absorption fibers
Through the combination of surface-modified rare earth doped cesium tungsten bronze and carboxymethyl cellulose, the color regulation limitations and compatibility problems of existing warm fibers are solved, and the preparation of multi-color optical fibers is realized, which improves the warmth performance of the fibers and The service life span meets consumers' demand for personalized and fashionable products.
Patent Information
- Application Number
- CN202411775057.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-05
- Publication Date
- 2025-01-03
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing warm fibers have limitations in color regulation, making it difficult to achieve diversified colors, and the compatibility and environmental impact of rare earth-based composite fibers are relatively large in the preparation process, which limits the fashion and practicality of textiles.
Using surface-modified rare earth doped cesium tungsten bronze, the bimetal doping ratio is adjusted by combining rare earth doped cesium tungsten bronze powder and carboxymethyl cellulose, and the multi-color absorbent fiber is prepared by combining ultrasonic treatment and high-temperature calcination technology. , achieves the diversity of fibers and efficient warmth.
The fiber color changes from green, blue to purple, improves the compatibility of rare earth-doped cesium tungsten bronze with polymers, reduces production costs and environmental burdens, and enhances the heat storage and heating performance of the fibers. Extends service life and combines colorful and efficient warmth.
Smart Images

Figure CN119243351A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of functional fibers, and in particular relates to a surface-modified rare earth-doped cesium tungsten bronze and its application in the preparation of multicolor light-absorbing fibers. Background Art
[0002] In the modern functional textile industry, the pursuit of more efficient and distinctive materials has become a major trend. This is especially true in the development of functional thermal insulation fibers, where market demand strongly favors lightweight, efficient, and customizable colors. Currently, the development of thermal insulation fibers largely focuses on single functions, such as heat storage or single-color heat generation, making it difficult to achieve color diversification at the raw material level. This limits the further integration of fashion and practicality in textiles.
[0003] Traditional tungsten bronze materials have been widely studied and used in thermal textiles. For example, patent CN105200546B discloses "A light-absorbing and heat-storing far-infrared fiber, its preparation method and application." This material has light-absorbing and heat-storing properties, but it mainly faces limitations in color control, usually requiring additional dyeing or post-processing to achieve multi-color effects. Furthermore, the development of rare-earth-based thermal composite fibers, such as patent CN114525595A which discloses "A rare-earth-based thermal composite fiber, its preparation method and application," while improving thermal insulation performance, still presents challenges in the compatibility and environmental impact of the composite materials during the preparation process. Summary of the Invention
[0004] In view of this, the present invention aims to overcome the defects in the prior art and proposes a surface-modified rare earth-doped cesium tungsten bronze and its application in the preparation of multicolor light-absorbing fibers.
[0005] To achieve the above objectives, the technical solution of the present invention is implemented as follows: In a first aspect, the present invention provides a surface-modified rare-earth-doped cesium tungsten bronze, which is prepared from raw materials including rare-earth-doped cesium tungsten bronze powder and carboxymethyl cellulose, wherein the concentration of the carboxymethyl cellulose aqueous solution is 0.1-0.5 wt%, and the mass ratio of the rare-earth-doped cesium tungsten bronze powder to the carboxymethyl cellulose aqueous solution is 1:(1-2).
[0006] Preferably, the surface-modified rare-earth-doped cesium tungsten bronze has the following structural formula: La x Cs y WO3@CMC, where 0 < 3x + y < 0.33.
[0007] The surface-modified rare-earth-doped cesium tungsten bronze La x Cs yWO3@CMC (0<3x+y<0.33) is green when x=0.01, y=0.2, blue when x=0.01, y=0.3, dark blue when x=0.08, y=0.05, and purple when x=0.05, y=0.01.
[0008] Preferably, the method for preparing the rare earth-doped cesium tungsten bronze powder is as follows: Step S1: Weigh out rare earth lanthanum source, cesium source and tungsten source and mix them to obtain mixed powder. Add deionized water, anhydrous ethanol or ethylene glycol as dispersion medium and ball mill in planetary ball mill for 3-6 hours. The ratio of the total mass of the mixed powder to deionized water is 1:(2-4). Step S2: The ball-milled slurry is dried at 80-110℃ for 12-24 hours, then ground and pulverized, and the resulting powder is sealed and stored. Step S3: Calcine the dried powder at 600-900℃ for 3-8 hours to obtain rare earth-doped cesium tungsten bronze powder.
[0009] Preferably, the molar ratio of lanthanum, cesium, and tungsten in the mixed powder is x:y:1.
[0010] Preferably, the rare earth lanthanum source is one or both of lanthanum chloride and lanthanum carbonate.
[0011] Preferably, the cesium source is one or both of cesium chloride and cesium carbonate.
[0012] Preferably, the tungsten source is one or a mixture of two or more of tungsten oxide, ammonium tungstate, ammonium paratungstate, and ammonium metatungstate.
[0013] Secondly, this invention also provides a method for preparing the above-mentioned surface-modified rare-earth-doped cesium tungsten bronze, the specific steps of which are: rare-earth-doped cesium tungsten bronze powder and carboxymethyl cellulose aqueous solution are kept in an ultrasonic water bath at 300-600W for 1-4 hours, and ammonia water is added dropwise to adjust the pH value to 8-10 to obtain surface-modified rare-earth-doped cesium tungsten bronze La. x Cs y WO3@CMC.
[0014] Thirdly, the present invention also provides a multicolor light-absorbing fiber, which is prepared by hot mixing, granulation and spinning of 20-70 parts by weight of light-absorbing slurry and 50-70 parts by weight of high molecular polymer.
[0015] Preferably, the light-absorbing paste is composed of surface-modified rare-earth-doped cesium tungsten bronze La. x Cs y It was prepared by combining WO3@CMC, deionized water, dispersant, and defoamer.
[0016] Preferably, the mass ratio of the light-absorbing paste raw material is as follows: La x Cs y WO3@CMC 10-50 parts, deionized water 40-80 parts, dispersant 5-10 parts, defoamer 0.5-1 part, of which La x Cs y The particle size of WO3@CMC is 100-800nm.
[0017] Preferably, the dispersant is one or a mixture of two or more of the following: silane coupling agent KH560, polyethylene glycol, sodium polyacrylate, sodium carboxymethyl cellulose, and alkyl polyglucoside.
[0018] Preferably, the defoamer is one or a mixture of two or more of AKN-3386, DF-2854, and P803.
[0019] Fourthly, the present invention also provides a method for preparing the above-mentioned multicolor light-absorbing fibers, comprising the following steps: After the light-absorbing slurry and the polymer are mixed evenly and dried to a moisture content of no more than 200 ppm, they are then placed in a twin-screw granulator. The polymer and the light-absorbing slurry are fully mixed at high temperature and then extruded and granulated to obtain light-absorbing functional masterbatch. Finally, the obtained light-absorbing functional masterbatch is spun by a melt spinning machine to obtain multi-color light-absorbing fibers.
[0020] Fifthly, the present invention also provides the application of the above-mentioned multicolor light-absorbing fibers in the textile field, particularly in the preparation of gloves, scarves, and tent fabrics.
[0021] Compared with the prior art, the present invention has the following advantages: (1) This invention adjusts La x Cs y The bimetallic doping ratio in WO3@CMC (0<3x+y<0.33) enables color variations from green, blue, and dark blue to purple at the fiber raw material end, meeting consumers' demands for personalized and fashionable products. This feature breaks through the color limitations of traditional tungsten bronze fibers and provides a wider range of application possibilities.
[0022] (2) The carboxymethyl cellulose (CMC) modification technology used in this invention not only improves the compatibility of rare earth-doped cesium tungsten bronze with polymers, but also reduces the environmental impact during production. Compared with traditional fibers that require subsequent dyeing or chemical treatment, this invention completes the imparting of color and function during the spinning process, significantly reducing production costs and environmental burden.
[0023] (3) The fibers of the present invention not only have visual diversity, but also achieve functional optimization. The modified rare earth doped cesium tungsten bronze enhances the heat storage and heat generation properties of the fibers, enabling them to effectively maintain a comfortable temperature in low-temperature environments, making them suitable for outdoor activities and wearing in cold environments.
[0024] (4) The fiber of the present invention is modified by CMC, and the dispersion of rare earth doped cesium tungsten bronze nanoparticles in the polymer matrix is improved, which effectively prevents precipitation or aggregation problems during washing and long-term use, thereby extending the service life of the fiber product and maintaining its functionality.
[0025] (5) The multicolor light-absorbing fiber of the present invention combines color diversity and efficient heat preservation function, so that the final product can be used across seasons, providing users with greater convenience and practicality. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 XRD patterns of rare earth-doped cesium tungsten bronze and lanthanum tungsten bronze in Examples 1-4 and Comparative Examples 1-6; Figure 2 The image shows the SEM image of the cross-section of the light-absorbing masterbatch in Application Example 1. DETAILED DESCRIPTION
[0027] Unless otherwise defined, the technical terms used in the following embodiments have the same meanings as commonly understood by those skilled in the art. Unless otherwise specified, the experimental reagents used in the following embodiments are conventional biochemical reagents; and the experimental methods described are conventional methods.
[0028] The present invention will be described in detail below with reference to the embodiments.
[0029] Example 1
[0030] Preparation of La 0.01 Cs 0.2 The specific steps for using WO3@CMC are as follows: (1) Lanthanum carbonate, cesium carbonate and ammonium tungstate were weighed and mixed in a molar ratio of La:Cs:W=0.01:0.2:1 to obtain a mixed powder. Then, deionized water was added in a planetary ball mill at a ratio of 1:3 to the total mass of the mixed powder. The mixture was then ball-milled for 3 hours.
[0031] (2) The slurry after ball milling is dried in a forced-air oven at 80°C for 24 hours until it is completely dry. Then it is ground and pulverized and sealed for storage.
[0032] (3) The dried powder was placed in a rotary tube furnace with dual-stage gas flow control and calcined at 600℃ for 3 hours to obtain rare earth-doped cesium tungsten bronze powder La. 0.01 Cs 0.2WO3.
[0033] (4) Rare earth-doped cesium tungsten bronze powder La 0.01 Cs 0.2 WO3 was added to a 0.5 wt% carboxymethyl cellulose aqueous solution and kept in a 300 W ultrasonic water bath for 1 hour. Rare earth-doped cesium tungsten bronze powder and carboxymethyl cellulose aqueous solution were mixed at a mass ratio of 1:1. Ammonia was added dropwise to adjust the pH to 8 to obtain La. 0.01 Cs 0.2 WO3@CMC.
[0034] Example 2
[0035] Preparation of La 0.01 Cs 0.3 The specific steps for using WO3@CMC are as follows: (1) The prepared La 0.01 Cs 0.3 Lanthanum carbonate, cesium carbonate, and ammonium tungstate were weighed and mixed to obtain a mixed powder with a molar ratio of La:Cs:W = 0.01:0.3:1. Then, deionized water was added at a ratio of 1:2 of the total mass of the mixed powder to deionized water, and the mixture was ball-milled in a planetary ball mill for 6 hours.
[0036] (2) The ball-milled slurry was dried in a forced-air oven at 110°C for 12 hours until it was completely dry. After grinding and crushing, it was sealed and stored.
[0037] (3) The dried powder was placed in a rotary tube furnace with dual-stage gas flow control and calcined at 700°C for 3 hours to obtain rare earth-doped cesium tungsten bronze powder.
[0038] (4) Rare earth-doped cesium tungsten bronze powder was added to a 0.3 wt% carboxymethyl cellulose aqueous solution and kept in a 600 W ultrasonic water bath for 1 h. The mass ratio of rare earth-doped cesium tungsten bronze powder to carboxymethyl cellulose aqueous solution was 1:1. Ammonia was added dropwise to adjust the pH to 10 to obtain La. 0.01 Cs 0.3 WO3@CMC.
[0039] Example 3
[0040] Preparation of La 0.08 Cs 0.05 The specific steps for using WO3@CMC are as follows: (1) The prepared La 0.08 Cs 0.05 Lanthanum chloride, cesium carbonate, and ammonium tungstate were weighed and mixed to obtain a mixed powder with a molar ratio of La:Cs:W = 0.08:0.05:1. Then, ethylene glycol was added according to the ratio of the total mass of the mixed powder to deionized water of 1:2, and the mixture was ball-milled in a planetary ball mill for 4 hours.
[0041] (2) The ball-milled slurry was dried in a forced-air oven at 100°C for 20 hours until it was completely dry. After grinding and crushing, it was sealed and stored.
[0042] (3) The dried powder was placed in a rotary tube furnace with dual-stage gas flow control and calcined at 700°C for 5 hours to obtain rare earth-doped cesium tungsten bronze powder.
[0043] (4) Rare earth-doped cesium tungsten bronze powder was added to a 0.2 wt% carboxymethyl cellulose aqueous solution and kept in a 400 W ultrasonic water bath for 1 h. The mass ratio of rare earth-doped cesium tungsten bronze powder to carboxymethyl cellulose aqueous solution was 1:2. Ammonia was added dropwise to adjust the pH to 9 to obtain La. 0.08 Cs 0.05 WO3@CMC.
[0044] Example 4
[0045] Preparation of La 0.05 Cs 0.01 The specific steps for using WO3@CMC are as follows: (1) The prepared La 0.05 Cs 0.01 Lanthanum carbonate, cesium carbonate, and ammonium tungstate were weighed and mixed to obtain a mixed powder with a molar ratio of La:Cs:W = 0.05:0.01:1. Then, anhydrous ethanol was added at a ratio of 1:4 between the total mass of the mixed powder and deionized water, and the mixture was ball-milled in a planetary ball mill for 6 hours.
[0046] (2) The ball-milled slurry was dried in a forced-air oven at 90°C for 22 hours until it was completely dry. After grinding and crushing, it was sealed and stored.
[0047] (3) The dried powder was placed in a rotary tube furnace with dual-stage gas flow control and calcined at 900°C for 5 hours to obtain rare earth-doped cesium tungsten bronze powder.
[0048] (4) Rare earth-doped cesium tungsten bronze powder was added to a 0.4 wt% carboxymethyl cellulose aqueous solution and kept in a 400 W ultrasonic water bath for 1 h. The mass ratio of rare earth-doped cesium tungsten bronze powder to carboxymethyl cellulose aqueous solution was 1:2. Ammonia was added dropwise to adjust the pH to 9 to obtain La. 0.05 Cs 0.01 WO3@CMC.
[0049] Comparative Example 1 Preparation of La 0.01 WO3, the specific steps are as follows: (1) The prepared La 0.01Lanthanum carbonate and ammonium tungstate were weighed and mixed to obtain a mixed powder. Then, deionized water was added at a ratio of 1:2 of the total mass of the mixed powder to deionized water, and the mixture was ball-milled in a planetary ball mill for 4 hours.
[0050] (2) The ball-milled slurry was dried in a forced-air oven at 80°C for 24 hours until it was completely dry. After grinding and crushing, it was sealed and stored.
[0051] (3) The dried powder was placed in a rotary tube furnace with dual-stage gas flow control and calcined at 900℃ for 5 hours to obtain lanthanum tungsten bronze powder (La). 0.01 WO3).
[0052] Comparative Example 2 Preparation of La 0.01 WO3@CMC, in which cesium carbonate was not added, and the specific steps are the same as in Example 1.
[0053] Comparative Example 3 Preparation of La 0.01 Cs 0.2 WO3, wherein no ammonium tungstate was added, and the specific steps are the same as in Example 1.
[0054] Comparative Example 4 Preparation of La 0.01 Cs 0.4 WO3@CMC, wherein lanthanum carbonate, cesium carbonate, and ammonium tungstate are weighed in a molar ratio of La:Cs:W=0.01:0.4:1; the specific steps are the same as in Example 1.
[0055] Comparative Example 5 Preparation of La 0.05 Cs 0.2 WO3@CMC, wherein lanthanum carbonate, cesium carbonate, and ammonium tungstate are weighed in a molar ratio of La:Cs:W = 0.05:0.2:1; the specific steps are the same as in Example 1.
[0056] Comparative Example 6 Preparation of La 0.01 Cs 0.2 WO3@CMC, wherein the concentration of the carboxymethyl cellulose aqueous solution is 0.6 wt%, and the remaining steps are the same as in Example 1.
[0057] Application Example 1 The specific steps for preparing multicolor light-absorbing fibers using rare-earth-doped cesium tungsten bronze are as follows: (1) Take the La prepared in Example 1 0.01 Cs 0.210 parts by weight of WO3@CMC, 5 parts by weight of silane coupling agent KH560, 40 parts by weight of deionized water, and 0.5 parts by weight of defoamer AKN-3386 were mixed evenly and then ultrasonically ground to about 300nm to obtain light-absorbing slurry. (2) Mix 20 parts by weight of light-absorbing slurry and 50 parts by weight of high molecular weight polymer polyurethane in a high-speed mixer until uniform; (3) After uniformly mixing the light-absorbing slurry obtained in step (2) with the polymer, dry it until the moisture content is no more than 200 ppm, and then put it into a twin-screw granulator. The polymer and the light-absorbing slurry are fully mixed by high temperature and then extruded and granulated to obtain the light-absorbing functional masterbatch (the SEM image of its cross section is shown in Figure 1). Figure 2 As shown in the figure, the obtained light-absorbing masterbatch is finally spun into multi-color light-absorbing fibers by melt spinning machine.
[0058] (4) The light-absorbing fibers were woven into plain weave fabric by a loom and their light-heat storage and temperature rise performance was tested.
[0059] Application Example 2 The specific steps for preparing multicolor light-absorbing fibers using rare-earth-doped cesium tungsten bronze are as follows: (1) Take the La prepared in Example 2 0.01 Cs 0.3 WO3@CMC 50 parts by weight, alkyl polyglucoside 10 parts by weight, deionized water 80 parts by weight, and defoamer P803 1 part by weight are mixed evenly, and then ultrasonically ground to about 500nm to obtain light-absorbing slurry. (2) Mix 70 parts by weight of light-absorbing slurry and 70 parts by weight of polyethylene terephthalate (PET) in a high-speed mixer until homogeneous; (3) After mixing the light-absorbing slurry obtained in step (2) with the polymer, dry it until the water content is no more than 200 ppm. Then put it into a twin-screw granulator, and use high temperature to fully mix the polymer and the light-absorbing slurry before extruding and granulating to obtain light-absorbing functional masterbatch. Finally, spin the obtained light-absorbing functional masterbatch through a melt spinning machine to obtain multi-color light-absorbing fibers.
[0060] (4) The light-absorbing fibers were woven into plain weave fabric by a loom and their light-heat storage and temperature rise performance was tested.
[0061] Comparative Application Example 1 The specific steps for preparing lanthanum-tungsten bronze fibers are as follows: (1) The La prepared in Comparative Example 1 0.01 40 parts by weight of WO3, 8 parts by weight of sodium polyacrylate, 80 parts by weight of deionized water, and 1 part by weight of defoamer P803 were mixed evenly and then ultrasonically ground to about 400 nm to obtain lanthanum tungsten bronze slurry. (2) Mix 50 parts by weight of lanthanum tungsten bronze and 60 parts by weight of polyethylene terephthalate in a high-speed mixer until homogeneous; (3) After the lanthanum tungsten bronze slurry obtained in step (2) is mixed evenly with the polymer, it is dried until the water content is not higher than 200 ppm. Then it is put into a twin-screw granulator. The polymer and the lanthanum tungsten bronze slurry are fully mixed by high temperature and then extruded and granulated to obtain light-absorbing masterbatch. Finally, the light-absorbing masterbatch is spun by a melt spinning machine to obtain lanthanum tungsten bronze fiber.
[0062] (4) The light-heat storage and temperature rise performance of lanthanum tungsten bronze fiber was tested by weaving it into plain fabric on a loom.
[0063] Comparative Application Example 2 The difference from Comparative Application Example 1 is that La prepared using Comparative Example 2 is used. 0.01 The specific steps for WO3@CMC are the same as those in Comparative Application Example 1.
[0064] Comparative Application Example 3 The difference from Comparative Application Example 1 is that La prepared using Comparative Example 3 is used. 0.01 Cs 0.2 WO3, the specific steps are the same as those in Comparative Application Example 1.
[0065] Comparative Application Example 4 The difference from Comparative Application Example 1 is that La prepared using Comparative Example 4 is used. 0.01 Cs 0.4 The specific steps for WO3@CMC are the same as those in Comparative Application Example 1.
[0066] Comparative Application Example 5 The difference from Comparative Application Example 1 is that La prepared using Comparative Example 5 was used. 0.05 Cs 0.2 The specific steps for WO3@CMC are the same as those in Comparative Application Example 1.
[0067] Comparative Application Example 6 The difference from Comparative Application Example 1 is that La prepared using Comparative Example 6 is used. 0.01 Cs 0.2 The specific steps for WO3@CMC are the same as those in Comparative Application Example 1.
[0068] Table 1. Performance Comparison of Fabrics in Application Examples and Comparative Application Examples
[0069] Comparing the maximum temperature rise performance of Application Examples 1-2 with that of Comparative Application Examples 1-6, after tests of 10 minutes of illumination and 10 minutes of light extinguishing, the photothermal heat storage temperature rise performance of Application Examples 1 and 2 was approximately 3°C higher than that of Comparative Application Examples 1-6. This indicates that the multicolor light-absorbing fibers prepared from CMC-modified rare-earth-doped cesium tungsten bronze have superior heat storage performance compared to rare-earth tungsten bronze fibers. This is because bimetallic tungsten bronze enhances the localized surface plasmon resonance, increasing the absorption rate in the near-infrared band, thus absorbing near-infrared energy and achieving the function of heat absorption and insulation. The surface modification of CMC improves the uniformity of rare-earth-doped cesium tungsten bronze in the fiber (see...). Figure 2 It is easier to spin.
[0070] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A surface modified rare earth doped cesium tungsten bronze, characterized in that: The rare earth doped cesium tungsten bronze powder and carboxymethyl cellulose aqueous solution are used as raw materials, wherein the concentration of the carboxymethyl cellulose aqueous solution is 0.1-0.5wt%, and the mass ratio of the rare earth doped cesium tungsten bronze powder to the carboxymethyl cellulose aqueous solution is 1: (1-2).
2. The surface modified rare earth doped cesium tungsten bronze according to claim 1, characterized in that: The structural formula of the surface modified rare earth doped cesium tungsten bronze is: La x Cs y WO3@CMC, where 0<3x+y<0.
33.
3. The surface modified rare earth doped cesium tungsten bronze according to claim 1, characterized in that: The preparation method of the rare earth doped cesium tungsten bronze powder is as follows: Step S1: weighing rare earth lanthanum source, cesium source and tungsten source, mixing to obtain mixed powder, adding deionized water, anhydrous ethanol or ethylene glycol as a dispersion medium, and ball milling in a planetary ball mill for 3-6 hours, wherein the ratio of the total mass of the mixed powder to the deionized water is 1: (2-4); Step S2: The ball-milled slurry is dried at 80-110° C. for 12-24 hours, and then ground and crushed to obtain a powder which is sealed and stored; Step S3: calcining the dried powder at 600-900° C. for 3-8 hours to obtain rare earth-doped cesium tungsten bronze powder.
4. The surface modified rare earth doped cesium tungsten bronze according to claim 3, characterized in that: The molar ratio of the lanthanum element in the rare earth lanthanum source, the cesium element in the cesium source and the tungsten element in the tungsten source is x:y:1; the rare earth lanthanum source is one or both of lanthanum chloride and lanthanum carbonate; the cesium source is one or both of cesium chloride and cesium carbonate; the tungsten source is one or both of tungsten oxide, ammonium tungstate, ammonium paratungstate and ammonium metatungstate. A mixture of one or more of these.
5. The method for preparing the surface modified rare earth doped cesium tungsten bronze according to any one of claims 1 to 4, characterized in that: The rare earth doped cesium tungsten bronze powder and carboxymethyl cellulose aqueous solution are kept in a 300-600W ultrasonic water bath for 1-4 hours, and ammonia water is added dropwise to adjust the pH value to 8-10 to obtain surface modified rare earth doped cesium tungsten bronze La x Cs y WO3@CMC.
6. A multicolor light-absorbing fiber, characterized in that: The multicolor light-absorbing fiber is prepared by hot mixing, granulating and spinning 20-70 parts by weight of light-absorbing slurry and 50-70 parts by weight of high molecular polymer; the light-absorbing slurry is composed of surface-modified rare earth-doped cesium tungsten bronze La x Cs y WO3@CMC, deionized water, dispersant and defoamer are prepared.
7. The multicolor light-absorbing fiber according to claim 6, characterized in that: The mass ratio of the light-absorbing slurry raw materials is as follows: La x Cs y WO3@CMC 10-50 parts, deionized water 40-80 parts, dispersant 5-10 parts, defoamer 0.5-1 parts, among which La x Cs y The particle size of WO3@CMC is 100-800nm.
8. The multicolor light-absorbing fiber according to claim 6, characterized in that: The dispersant is one or a mixture of two or more of silane coupling agent KH560, polyethylene glycol, sodium polyacrylate, sodium carboxymethyl cellulose, and alkyl polyglucoside; the defoamer is one or a mixture of two or more of AKN-3386, DF-2854, and P803.
9. The method for preparing a multicolor light-absorbing fiber according to claim 8, characterized in that: The following steps are involved: The light-absorbing slurry and the high molecular polymer are mixed evenly and then dried to a water content of no more than 200ppm, and then placed in a twin-screw granulator. The high molecular polymer and the light-absorbing slurry are fully mixed by high temperature and then extruded and granulated to obtain light-absorbing functional masterbatch. Finally, the obtained light-absorbing functional masterbatch is spun by a melt spinning machine to obtain multi-color light-absorbing fibers.
10. Use of the multicolor light-absorbing fiber according to any one of claims 6 to 8 in the textile field.
Citation Information
Patent Citations
Surface hydrophilically-modified rare-earth-doped luminescent material and anti-falsification paper containing same
CN108913128A
Hydrogel material with shape memory function and preparation and application thereof
CN112375258A
Cellulose-based binuclear rare earth organic polymer composite material with controllable fluorescence as well as preparation method and application of cellulose-based binuclear rare earth organic polymer composite material
CN114276801A
Nanometer multi-metal doped tungsten bronze heat storage fiber and preparation method thereof
CN117448980A
Rare earth composite nano ceramic antibacterial material based on visible light photocatalysis
CN118177218A
Cited By
Preparation method of rare earth doped tungsten powder for tungsten wire diamond wire
CN121131777A
